UPAYA PEMBERDAYAAN MASYARAKAT OLEH RUMAH KREATIF WADAS KELIR MELALUI PENGUATAN LITERASI - Khofifah Hany Amaria; Nur Hafidz (Direktorat Pendidikan Masyarakat dan Pendidikan Khusus, Direktorat Jenderal PAUD, Pendidikan Dasar, dan Pendidikan Menengah, 2021)
Community empowerment is a community dedication to devote and perpetuate a social activity in order to improve environmental conditions. In this effort, this research focuses on the process of community empowerment based on literacy. Literacy culture that is driven through reading, writing, and critical thinking for the community's ability to deal with the problems of the dynamics of life. The process of literacy culture for the community does take a long time so this research focuses on empowering literacy through strengthening literacy. This research uses descriptive qualitative method in its analysis. The object of this research is the Wadas Kelir Creative House (RKWK) in Karangklesem Village, Purwokerto. Techniques in taking data sources by observation, interviews and documentation. As a result, the empowerment process at the Wadas Kelir Creative House (RKWK) has good and creative potential. This is because the impact of literacy has a positive effect on society in increasing the learning potential of children, adolescents, and parents. The efforts of the surrounding community to have capacity building through open knowledge and service activities programs, creativity in skills, and enriching their potential by working. From here, the impact of literacy can be seen from: 1) Children, adolescents, and parents have work and achievements, 2) High learning potential, 3) and have scientific benefits to become PAUD Tutors, open boarding houses, to run the economy with good.